2013
DOI: 10.1111/cge.12258
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased next generation sequencing analysis confirms the existence of autosomal dominant Alport syndrome in a relevant fraction of cases

Abstract: The mode of inheritance of Alport syndrome (ATS) has long been controversial. In 1927, the disease was hypothesized as a dominant condition in which males were more severely affected than females. In 1990, it was considered an X-linked (XL) semidominant condition, due to COL4A5 mutations. Later on, a rare autosomal recessive (AR) form due to COL4A3/COL4A4 mutations was identified. An autosomal dominant (AD) form was testified more recently by the description of some large pedigrees but the real existence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 16 publications
(24 reference statements)
7
121
0
Order By: Relevance
“…Hearing loss was observed in 48% and ocular changes in 14% of the patients tested, while nearly all had ultrastructural GBM findings pathognomonic of AS. Interestingly, no FSGS was reported in this Italian cohort [31]. FSGS was not reported in additional cohorts of patients with heterozygous COL4A3/A4 mutations either, mainly from Italy.…”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 81%
See 1 more Smart Citation
“…Hearing loss was observed in 48% and ocular changes in 14% of the patients tested, while nearly all had ultrastructural GBM findings pathognomonic of AS. Interestingly, no FSGS was reported in this Italian cohort [31]. FSGS was not reported in additional cohorts of patients with heterozygous COL4A3/A4 mutations either, mainly from Italy.…”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 81%
“…Some authors have even reported that these patients with heterozygous mutations show autosomal dominant Alport syndrome (ADAS), since they described the ultrastructural pathognomonic features of the GBM, in addition to familial MH and proteinuria. Fallerini et al [31 ]reported on a cohort of heterozygous patients of whom 58% presented with proteinuria and 27.5% progressed to ESRD at a mean age of 56 years. Hearing loss was observed in 48% and ocular changes in 14% of the patients tested, while nearly all had ultrastructural GBM findings pathognomonic of AS.…”
Section: Tbmn and Accompanied Fsgs In The Molecular Genetics Eramentioning
confidence: 99%
“…Ten patients were considered as likely affected with BFH (however, in families 57 and 79, only women were affected), because individuals in at least two generations presented with isolated hematuria (without proteinuria or renal failure). One woman (40) presented with sporadic isolated hematuria without proteinuria. Supplemental Table 1 shows the clinical, biologic, and morphologic information, modified Flinter scoring (Concise Methods), and suspected mode of inheritance for each proband.…”
Section: Patients' Phenotypes and Mode Of Inheritancementioning
confidence: 99%
“…37 Analysis of our cohort for those criteria is shown Table 7, and the score of each patient is shown in Supplemental Table 1. Altogether, 4 index cases fulfilled four criteria, 14 index cases fulfilled three criteria, 38 index cases fulfilled two criteria, 43 index cases fulfilled one criterion (including 10 patients considered as BFH), and 2 index cases had zero criteria (one women [40] with sporadic hematuria and thin basement membrane and one man [42] with hematuria and proteinuria without hearing or eye defect and without known family history of renal disease). Surprisingly, two men had a discontinuous expression of the a5 (IV) in the skin BM.…”
Section: Patientsmentioning
confidence: 99%
“…One way to overcome these problems is to sequence all three genes simultaneously using NGS-targeted sequencing 14 . We present a new, efficient, amplicon based NGS protocol for simultaneous analysis of the coding regions (all the exons and flanking intronic sequences) of the COL4A3, A4 and A5 genes since a previously published NGS-based approach failed to detect mutations in 45% of their cases 11 . Both mutations and polymorphisms in the 3 investigated COL4A genes are thought to be highly population-specific due to the lack of selection pressure in case of the polymorphisms and low selection pressure in case of TBMN.…”
Section: Introductionmentioning
confidence: 99%